Proximate Characteristics of Tofu Dregs Flour as an Alternative Food Ingredient - Rizki Aristyarini; Andriyana Gustam; Fitrawaty Orista Evar; Suryansyah Surahman; Husnul Hatimah (G-Tech: Jurnal Teknologi Terapan, 2025)
Tofu dregs is an abundant waste from food production that is often not optimally utilized. In fact, tofu dregs have the potential to become an alternative food source if done in accordance with the ideal processing process and supported by the characterization of its nutritional content. This study aims to assess the chemical characteristics of tofu dregs flour through proximate analysis. The parameters analyzed included moisture content, ash, fat, protein, and carbohydrate by difference. Tofu dregs samples were obtained from tofu artisans in Bogor Regency, then dried, ground, and analyzed through the laboratory. The research was exploratory in nature using two replicates. The results showed that the moisture content of tofu dregs flour was 8.49 ± 1.34%, ash content 2.81 ± 0.19%, fat 7.86 ± 0.21%, protein 17.32 ± 0.27%, and carbohydrate by difference 63.53 ± 1.09%. The high protein content indicates that most of the soybean protein fraction is still left in the dregs. The low moisture content means the potential microbiological resistance of tofu bagasse flour during storage. These findings confirm that tofu dregs flour has promising nutritional value and it can be further developed as a sustainable ingredient for high-protein and fiber-rich food formulations. This will thereby contribute to waste reduction and functional food innovation.